Penerapan Model Pembelajaran Hands on Activity dengan Media Handmade untuk Meningkatkan Motivasi Belajar Matematika - Putri, Yiyin Ivana; Ulya, Vita Fitriatul (FAKULTAS AGAMA ISLAM UNIVERSITAS BILLFATH, 2023)
The lack of students' motivation towards learning mathematics is caused by various factors, including the use of traditional and conventional teaching models. This study aims to determine the application of the hands-on activity learning model with the help of handmade media, such as origami paper material, to increase student learning motivation in mathematics lessons. The research method carried out is Classroom Action Research (CAR) which consists of two cycles, each with 4 stages. The subject of his research was a grade V student at MI Hidayatus Shibyan Jatirogo. The results showed that with the hands-on activity model, student learning motivation increased from cycle I by 57.14% and increased to 71.42% in cycle II. Meanwhile, student learning outcomes in the first cycle were 71.4% and increased by 85.7% in cycle II. If the application of this hands-on activity model is carried out by teachers continuously, better learning outcomes will be obtained and students will always be motivated to participate in mathematics lessons.